KEANEKARAGAMAN JENIS BURUNG DI TAMAN NASIONAL BETUNG KERIHUN KABUPATEN KAPUAS HULU, PROVINSI KALIMANTAN BARAT - Insan Kurnia; Hendrio Fadly; Udi Kusdinar; Wawan G Gunawani; Dwi W Idaman; Rika S Dewi; Dwi Yandhi; Grace S Saragih; Gilang F Ramdhan; Tyas D Djuanda; Ruri Risnawati; Muhammad Firdaus (Media Konservasi, 2005)
This observation objection to cover bird diversity in Sibau Watershed, Betung Kerihun National Park (BKNP). The observation was done in along river (Sibau Rill, Sibau River, Apyang River, Menyakan River) and hill (Menyakan Hulu Hill and Apyang Hill) and point at transect. That habitat is riverine. Amount of bird was found are 93 species from 31 family with 39 species new record for Sibau Watershed. The large abundance is Edible-nest Swiftlet (Collocalia fuciphaga), and than folowwed by Asian Palm-swift (Cypsiurus balasiensis) and Whiskered Treeswift (Hemiprocne comata). The total individu was found is 660 individu with vaule of diversity index is 3.7618 and evennes index is 0.8299. The five bird species is endemic to the Borneo, one species is Appendix I CITES, 13 species is Appendix II CITES, 26 species is protected, and five species is treathened.